2018
DOI: 10.1136/tsaco-2018-000196
|View full text |Cite
|
Sign up to set email alerts
|

Banning open carry of unloaded handguns decreases firearm-related fatalities and hospital utilization

Abstract: BackgroundSince 1967, in California it has been illegal to openly carry a loaded firearm in public except when engaged in hunting or law enforcement. However, beginning January 1, 2012, public open carry of unloaded handguns also became illegal. Fatal and non-fatal (NF) firearm injuries were examined before and after adoption of the 2012 ban to quantify the effect of the new law on public health.MethodsState-level data were obtained directly from California and nine other US state inpatient and emergency depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The cumulative results would suggest that, when taking into account other significant associations such as socioeconomic factors, open carry legality is not directly associated with the firearm death rate. That said, one study did link the banning the open carry of unloaded handguns to decreased fatality rates [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative results would suggest that, when taking into account other significant associations such as socioeconomic factors, open carry legality is not directly associated with the firearm death rate. That said, one study did link the banning the open carry of unloaded handguns to decreased fatality rates [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Callcut et al found banning open carry of unloaded handguns in California (where open carry of loaded guns is already illegal) to a decreased death rate [ 36 ]. Their finding, though, was based on a change in the law in a single state, which does limit the generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information, however, regarding the impact of these laws on nonfatal firearm injury. To our knowledge, only one published study examines the impact of state firearm laws on nonfatal firearm-related injuries 11 . That study examined the effects of a single law (open carry of handguns) in a single state (California) 11 .…”
mentioning
confidence: 99%
“…11 That study examined the effects of a single law (open carry of handguns) in a single state (California). 11 Almost uniformly, however, broad studies of the effects of changes in state firearm laws have been performed in the context of fatalities alone. Since the majority of firearm injuries are nonfatal, 1 this greatly limits our understanding of the implications of firearm-related policy.…”
mentioning
confidence: 99%
See 1 more Smart Citation